Economic and Social Survey of Asia and the Far East 1956 - United Nations Economic; Social Commission for Asia; the Pacific (United Nations, 1956)
This latest edition of the Survey analyzes current economic and social developments in the region against the background of events in the world economy. It also focuses on the serios problems of growth and transformation of the area's least developed and Pacific Island developing economies.